Post-adoption buffering effects of innovative product aesthetics - Christian Nagel; Jan H. Schumann (Creativity and Innovation Management, 2020)
Innovative aesthetic product appearances can create buffering effects in the pre-adoption phase that lead consumers to base their expectations on the aesthetics rather than on objective information about innovative products. How do innovative aesthetics influence product experience in the post-adoption phase? Using longitudinal post-adoption data from early adopters of an electric car model, this study shows that consumers' perceptions of innovative aesthetic value buffer the effect of product-related hedonic experience on attitudes towards the product. The more value consumers derive from innovative product aesthetics post-adoption, the less they ground their attitudes on actual hedonic experience. Product managers thus should opt for designs that grant aesthetic utility over time. Innate consumer innovativeness levels moderate the buffering effect, such that the effect of aesthetic innovative product evaluations on the relationship between experienced hedonic utility and attitude is stronger for more innovative consumers. Innovative consumers are especially sensitive to innovative aesthetic value, so in their co-creation efforts, managers should seek out these customers, because doing so can increase early adopters' long-term product satisfaction and word of mouth, both of which expand the breadth of diffusion for the innovations.
Keywords: 330; buffering; hedonic; innovation; innovative aesthetics